Efek Fitokimia Bunga Marigold (Tagetes erecta) Terhadap Fotoaging: Tinjauan Literatur Sistematis - Ni Putu Windi Sukma Putri; Agus Eka Darwinata; Ni Made Linawati (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Photoaging is a major contributor to premature skin aging and is primarily caused by chronic exposure to ultraviolet (UV) radiation. UV induced oxidative stress, inflammation, and extracellular matrix degradation result in wrinkles, pigmentation, and loss of skin elasticity. This systematic review aimed to evaluate the phytochemical mechanisms of Tagetes erecta and assess its potential clinical relevance in preventing photoaging. A systematic literature search was conducted in PubMed, Science Direct, and Europe PMC for studies published between 2016 and 2026, following PRISMA 2020 guidelines. Studies were included if they investigated Tagetes erecta or phytochemical compounds known to be present in Tagetes erecta (e.g., lutein, zeaxanthin, flavonoids, phenolic acids) in UV-induced photoaging models. The findings indicate that Tagetes erecta contains bioactive compounds that reduce reactive oxygen species (ROS), enhance endogenous antioxidant defenses, suppress matrix metalloproteinase (MMP) expression, and preserve collagen integrity. Clinical studies evaluating carotenoids and related phytochemicals also found in Tagetes erecta reported improvements in minimal erythema dose, skin elasticity, hydration, pigmentation, and wrinkle appearance. Notably, only one study directly investigated Tagetes erecta in the context of photoaging, however, the available evidence is still limited and insufficient to establish strong clinical conclusions. Therefore, current clinical evidence remains largely indirect. Overall, Tagetes erecta represents a promising phytochemical source with strong mechanistic support, although further well-designed clinical studies are required.